Clinical application and research progress of condylar motion tracing analysis - WANG Chang, WANG Wenhui, ZHU Ruimin, WANG Bingjie, LIU Yanchu, ZHAO Jing, ZHOU Weina, CHEN Yinan, JI Qi, WANG Chen (Kouqiang yixue)
The condylar movement trajectories in healthy people usually have relatively consistent characteristics, while the change of the trajectory of the temporomandibular condyle often indicates the occurrence of various oral diseases. An in-depth understanding of the condylar movement can help physicians diagnose and evaluate the efficacy of oral diseases. This article reviews the development of condylar motion tracing technique, and introduces the research progress and clinical application status of condylar motion tracing analysis in various oral diseases. At the same time, the limitations of the current condylar motion tracing technique and the prospect of future clinical application are proposed.